Pengaruh Pemberian Teknik Ice Breaker terhadap Hasil Belajar Tematik Siswa Kelas V UPTD SD Negeri 122390 Pematangsiantar - Christin Letare Sihombing (Medan Resource Center, 2022)
This study was conducted to determine the effect of the ice breaker technique on the learning outcomes of fifth grade students of UPTD SD Negeri 122390 Pematangsiantar. This research method is a quasi-experimental quantitative research (quasi-experimental). To determine the sample, the author uses a saturated sampling type which is divided into two groups, namely the control group (class V-A) and the experimental group (class V-B) with each class having the same number of students, namely 30 students. Data collection techniques in this study are observation, test (multiple choice) and documentation. The author manages and analyzes the data with the help of SPSS 21.0 for Windows. The results of the normality and homogeneity tests carried out in the cognitive domain, it was found that the two sample classes were normal and had homogeneous variances. The results showed that the average value of the control class pre-test was 33.50, while the control class's post-test average was 45.00. And the average value of the experimental class pre-test was 34.00, while the post-test average value of the experimental class was 73.17. To determine the effect of giving the ice breaker technique on learning outcomes, data analysis was carried out using the t-test (independent sample t-test). The result shows the value of sig.(2-tailed) 0.000 < 0.05, so H0 is rejected and H1 is accepted. Thus, there is an effect of giving the ice breaker technique on the thematic learning outcomes of the fifth grade students of UPTD SD Negeri 122390 Pematangsiantar.